Implementasi aplikasi Audit Tools Linked Archive Systems (ATLAS) pada kantor akuntan publik di Kota Padang: Tingkat optimalisasi dan tantangan awal - Milluspitasari, Milluspitasari; Sudiman, Josephine; Dwiharyadi, Anda (Akuntansiku, 2025)
Digital transformation in the auditing sector encourages Public Accounting Firms (PAFs) to adopt computer-assisted auditing technologies. One of the major innovations developed by the Indonesian Institute of Certified Public Accountants (IAPI) and the Financial Professional Development Center (FPDC) is the Audit Tools and Linked Archive System (ATLAS). This study aims to describe the implementation and optimization levels of ATLAS and identify the initial challenges faced by auditors in PAFs across in Padang City. Using a quantitative descriptive approach, questionnaires were distributed to 75 auditors across different positions. The findings indicate that although most firms are familiar with ATLAS, its usage remains suboptimal. Only a minority of auditors apply ATLAS intensively, while the majority use its features partially. Key challenges include application complexity, limited training, resistance to change, and infrastructure constraints. These findings provide empirical insights into the real conditions of ATLAS implementation in regional areas and form the basis for future strategies to enhance the adoption of digital audit technologies.